OPTICAL MONITORING OF NGC 4151: BEGINNING OF SECOND CENTURY - Oknyanskij, V.; Metlova, N.; Artamonov, B.; Ezhkova, O.; Lyuty, A.; Lyuty, V. (Одеські астрономічні публікації, 2012)
We present the historical light curve of NGC 4151 for 1906 - 2012. The light curve (Oknyanskij anf Lyuty, 2007) is primarily based on our published photoelectric data (1968 - 2007, about 1040 nightly mean measurements) and photographic estimates (mostly Odessa and Moscow plates taken in 1906-1982 (Oknyanskij, 1978, 1983), about 350 measurements). Additionally, we include all data obtained prior to 1968 (de Vaucouleurs and de Vaucouleurs, 1968; Sandage, 1967; Wisniewski and Kleinmann, 1968; Fitch et al., 1967) in total, 19 photoelectric observations from 1958- 1967, reduced by us to the same diaphragm aperture as that used in our measurements) as well as photographic data (Pacholczyk et al., 1983) (Harvard and Steward observatories’ patrol plates taken in 1910-1968, about 210 measurements). The light curve includes our new photoelectrical and CCD data obtained during last 5 years. All these data were reduced to an uniform photometric system.